Senator North - Atherton, Gertrude Franklin Horn, 1857-1948 (Salt Lake City, UT : Project Gutenberg, 2004)
"Senator North" by Gertrude Franklin Horn Atherton is a novel written during the late 19th century. The story revolves around Betty Madison, a Southern woman who has recently returned to Washington after spending time abroad and is determined to engage with the political landscape, contending against her mother's traditional views regarding politicians. As she prepares to delve into the world of politics, she expresses her admiration for influential figures like Senator North, highlighting her desire to break free from the frivolities she perceives in society. The opening of the book introduces readers to Betty's character and her relationship with her mother, who represents the old-world Southern values. Betty's ambition to understand and participate in politics marks a significant shift in her life as she seeks to move beyond the constraints of societal expectations. The scenes showcase Betty's candid conversations with her mother and their views on the politicians of the time, setting up her quest for knowledge and connection with the prominent men in the Senate, including her fascination with Senator North. Atherton's writing paints a vivid picture of the societal dynamics within the political realm of Washington, hinting at complexities in character interactions that will unfold as the story progresses. (This is an automatically generated summary.)
Release date is 2004-07-01
Produced by Cedric Vonck, Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Political fiction; Washington (D.C.) -- Fiction; Legislators -- Fiction